The development of a curling simulation for performance improvement based on a physics engine - Heo, M.-H.; Kim, D. (Procedia Engineering, 2013)
In curling, the strategy and tactics of game management are the most important elements of athletic performance for players. Players with good performance must be able to have fast situational judgment and the ability to perform suitable skills in particular cases. Training for various strategies and skills are very important. Based on these conditions, in this paper we will analyze the characteristics of curling and develop a curling simulator which can be used as a training tool to increase performance in actual games. We will also discuss the process of developing curling simulation. When curling simulation based on physics engine is designed as an actual game as much as possible, it can help player to increase the performance with visual training in various circumstances and with no limitation of training space. Additionally, visualization with 3D animation can help the players understand intuitively. This curling simulation is developed as a program which can run on tablet (smart pad), making it available to use anywhere.